A revision of the genus Morphostenophanes Pic, 1925 (Coleoptera, Tenebrionidae, Stenochiinae, Cnodalonini) - Zhou, De-Yao (Zootaxa, 2020)
The genus Morphostenophanes Pic, 1925 is redefined and revised. Seventeen new species and three new subspecies are described, including M. aenescens yelang Zhou, new subspecies, M. bannaensis Zhou, new species, M. brevigaster Zhou, new species, M. chongli Zhou, new species, M. crassus Zhou, new species, M. furvus Zhou, new species, M. furvus weishanus Zhou, new subspecies, M. gaoligongensis Zhou, new species, M. iridescens Zhou, new species, M. lincangensis Zhou, new species, M. linglong Zhou, new species, M. metallicus Zhou, new species, M. minor, Zhou, new species, M. planus Zhou, new species, M. purpurascens Zhou, new species, M. sinicus Zhou, new species, and M. yunnanus Zhou, new species from Yunnan, China; M. chongli glaber Zhou, new subspecies from Yunnan, China and North Vietnam; M. curvitibialis Zhou, new species from Guangxi, China, and M. luoxiaoshanus Zhou, new species from Hunan, Hubei and Jiangxi, China. M. birmanicus (Kaszab, 1980) is recorded from China (Yunnan) for the first time. M. papillatus Kaszab, 1941 is firstly recorded from Yunnan and Sichuan, China. Two poorly known species, M. aenescens Pic, 1925 and M. vietnamicus Kaszab, 1980 are redescribed. Male of M. atavus (Kaszab, 1960) is described in detail. Misidentifications of M. aenescens Pic. 1925 and M. atavus (Kaszab, 1960) in previous works are corrected. Six species groups are proposed. A species catalog, identification key and distributional maps for the genus are given.